IMPLEMENTASI SISTEM PENILAIAN DALAM KURIKULUM 2013 DI SMA NEGERI 2 PEKANBARU - Zulian Vina Kurnia Kastina; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Implementation of assessment system of curriculum 2013 in Senior High School 2 Pekanbaru experiencing various problems because teachers and students are still not understand the assessment standards in curriculum 2013 due to the complicated and many assessment aspects, next still intertwined limited communication between the government and the school about assessment scale and the government still often changing regulations on the assessment system. The purpose of this research was to analyze how the implementation of assessment system of the curriculum 2013 at the Senior High School 2 pekanbaru and the factors that influence the implementation of assessment system of the curriculum 2013.This research using Van Meter and Van Horn theory which states that the successful implementation of a policy is the standart and policy objectives, resources, characteristic of the implementing organization, the communication between organization, the attitude of the implementing policies and social environment, economic and political. The method used is descriptive qualitative methods. Techniques of collecting data through observation, interviews and documentation, and techniques of analysis data through interactive analysis model by Miles and Huberman.The result showed that the implementation of assessment system of curriculum 2013 in Senior High School 2 Pekanbaru has not been done well and optimally because there are still many problems in the assessment system of curriculum 2013 is implemented in senior high school 2 pekanbaru. There are several factors that affecting the implementation of assessment system of curriculum 2013 in Senior High School 2 Pekanbaru has not been done well and optimally is the human resources, the attitude of the implementers and policy objectives and communication between implementers.Key Words: Implementation, Assessment System of Curriculum 2013, Senior High School